2008
DOI: 10.1002/art.23458
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a novel aggrecan‐degrading activity in cartilage: Studies of mice deficient in both ADAMTS‐4 and ADAMTS‐5

Abstract: Objective. To characterize aggrecan catabolism and the overall phenotype in mice deficient in both ADAMTS-4 and ADAMTS-5 (TS-4/TS-5 ⌬-cat) activity.Methods. Femoral head cartilage from the joints of TS-4/TS-5 ⌬-cat mice and wild-type mice were cultured in vitro, and aggrecan catabolism was stimulated with either interleukin-1␣ (IL-1␣) or retinoic acid. Total aggrecan release was measured, and aggrecanase activity was examined by Western blotting using neoepitope antibodies for detecting cleavage at EGE 373 Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 51 publications
(91 reference statements)
3
51
0
Order By: Relevance
“…5B). Hypertrophic chondrocytes also promote the destruction of growth plate cartilage by expression of a number of catabolic enzymes, including the matrix metalloproteinases (MMPs) MMP13 (Johansson et al, 1997) and MMP9 (Shinoda et al, 2008;Golovchenko et al, 2013) and the aggrecanases ADAMTS4 and ADAMTS5 (Glasson et al, 2004;Rogerson et al, 2008). We reasoned that, since ephrin B2 deletion was targeted to osteoblasts and chondrocytes, the lack of cartilage destruction in Osx1Cre.…”
Section: Resultsmentioning
confidence: 99%
“…5B). Hypertrophic chondrocytes also promote the destruction of growth plate cartilage by expression of a number of catabolic enzymes, including the matrix metalloproteinases (MMPs) MMP13 (Johansson et al, 1997) and MMP9 (Shinoda et al, 2008;Golovchenko et al, 2013) and the aggrecanases ADAMTS4 and ADAMTS5 (Glasson et al, 2004;Rogerson et al, 2008). We reasoned that, since ephrin B2 deletion was targeted to osteoblasts and chondrocytes, the lack of cartilage destruction in Osx1Cre.…”
Section: Resultsmentioning
confidence: 99%
“…Despite combinatorial deletion of five alleles of three Adamts genes in mice (Adamst5, Adamts20, and Adamts9), skeletal muscle dysfunction was not elucidated (20). Adamts4 and Adamts5 combinatorial knockout mice have been previously reported as having no overt skeletal muscle myopathy (20,47) further suggesting a compensating role for Adamts15 during skeletal muscle development.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the role of ADAMTS-4 as aggrecanase appears more evident in humans [441,442]. It has then been observed that ADAMTS-4 mRNA is induced in chondrocytes by IL-1 [443], while Adamts-4/Adamts-5 double knockout mice are protected from cartilage degradation by IL-1, but not by retinoic acid, suggesting that other aggrecans apart from ADAMTS-4 and -5 are capable of retinoic acid-induced cartilage breakdown, at least in animal models [444]. In addition, suppressing ADAMTS-4 and/or ADAMTS-5 in human cartilage explants, via transfection of these ADAMTSs by siRNAs, significantly decreased aggrecan release and catabolism induced by a combination of IL-1 , TNF-and oncostatin M [441].…”
Section: Metalloproteinases and Osteoarthritismentioning
confidence: 99%